Judgment Considerations Analysis On Case No. 2531K / PID SUS / 2018 - Sukino Sukino; Wasis Susetio (Penerbit Kemala Indonesia, 2021)
Corruption in Indonesia is widespread in society and continues to increase from year to year. Both in terms of the number of cases and the number that have occurred and state financial losses as well as in terms of more systematic crimes committed. The abuse of authority in the Corruption Eradication Law creates a gray area where official policies can have a criminal law dimension, with abuse of authority which is a form of maladministration and becomes a personal responsibility. abuse of authority requires that the perpetrator must be civil servants / state administrators. Research methods are used in this thesis writing, the type of research in this thesis is Normative research. Normative Law Research is to examine the principles of criminal law through literature study and what is used are materials related to the title of the thesis such as books, laws and regulations that will be reviewed and studied. because it is only the Civil Servant or State Officials who are authorized to abuse their authority in relation to their Position or Position in government. according to the author, in this matter or at least the panel of judges in imposing a criminal sentence on the defendant should have declared that the judge was proven guilty of abuse of power as indicted in the subsidair indictment. Defendant as a Civil Servant Position as Proxy of Budget User and Commitment Making Officer is the use of authority for procurement of goods and services based on authority, procedure, substance. Of the 10 (ten) Court Decisions, the Application of Criminal Imposition against the defendant / perpetrator a civil servant who has a position or position in the procurement of goods and services as a budget User or Budget User Proxy (KPA), the panel of judges imposes a criminal based on legal considerations, namely 6 (six) proven guilty of committing a criminal act of corruption violating Article 3 (elements of abuse of power) of Law Number 31 of 1999 and which is combined with Law Number 20 of 2001 concerning amendments to the Law concerning Eradication of Corruption as in the indictment of the Criminal Code of Prison 1 (one) year to 3 (three) years and a fine of Rp. 50,000,000 (fifty million rupiah). Meanwhile, 4 (four) were found guilty of committing a criminal act of corruption violating article 2 (against the law) of Law Number 31 of 1999 which was combined with Law Number 20 of 2001 concerning amendments to the Law on Eradicating Corruption as indicted in the indictment. Primary Criminal imprisonment of 4 (four) years to 5 (five) years and a fine of IDR 200,000,000 (two hundred million rupiah). So, if it is seen that the imposition of criminal article 3 (three) is relatively lighter so that it does not provide a deterrent effect, it should be heavier, at least 5 (five) years because the perpetrator is an ASN who has a position or position. Article 3 should be revised imprisonment to be a minimum of 5 (five) years.